2012
DOI: 10.1007/s00382-012-1603-x
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous responses of East Asian and Indian summer monsoons to mountain uplift shown by regional climate modelling experiments

Abstract: It has been demonstrated in climate models that both the Indian and East Asian summer monsoons (ISM and EASM) are strengthened by the uplift of the entire Asian orography or Tibetan Plateau (TP) (i.e. bulk mountain uplift). Such an effect is widely perceived as the major mechanism contributing to the evolution of Asian summer monsoons in the Neogene. However, geological evidence suggests more diachronous growth of the Asian orography (i.e. regional mountain uplift) than bulk mountain uplift. This demands a re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 80 publications
(118 reference statements)
8
88
2
1
Order By: Relevance
“…Wu et al [77], through numerical experiments by only considering the dynamic and thermal effects of the Iranian Plateau (the TP excluded), found that the monsoon circulation in the South Asian region south of 20°N was mainly regulated by the land-sea thermal contrast, while to the north it was controlled by the thermal forcing of the Iranian Plateau, showing considerable effects of the Iranian Plateau in maintaining the South Asian monsoon. The sub-regional climatic simulation by Tang et al [79] also indicated that the Iranian Plateau would promote the development of the South Asian summer monsoon and constrain the East Asian summer monsoon.…”
Section: Contributions Of Other Tectonic Movements To the Establishmementioning
confidence: 98%
See 2 more Smart Citations
“…Wu et al [77], through numerical experiments by only considering the dynamic and thermal effects of the Iranian Plateau (the TP excluded), found that the monsoon circulation in the South Asian region south of 20°N was mainly regulated by the land-sea thermal contrast, while to the north it was controlled by the thermal forcing of the Iranian Plateau, showing considerable effects of the Iranian Plateau in maintaining the South Asian monsoon. The sub-regional climatic simulation by Tang et al [79] also indicated that the Iranian Plateau would promote the development of the South Asian summer monsoon and constrain the East Asian summer monsoon.…”
Section: Contributions Of Other Tectonic Movements To the Establishmementioning
confidence: 98%
“…[79] Only the Himalayas and adjacent narrow terrain were retained, and the surface sensible heat flux from the Himalayas or from the plain of south of the plateau was suppressed.…”
Section: Effects Of Himalayan-tibetan Plateau Sub-regional Uplift On mentioning
confidence: 99%
See 1 more Smart Citation
“…Several adjustments to the deep convection scheme have been introduced since Gregory and Rowntree (1990), such as the addition of down-drafts (Gregory and Allen 1991), convective momentum transport using a flux gradient approach (Stratton et al 2009) and a convective available potential energy (CAPE) closure scheme, based on Fritsch and Chappell (1980a, b), which uses a dilute CAPE calculation. In the default MetUM GA3 configuration, the time scale for the CAPE closure is set at 90 min unless large-scale vertical velocities over 0.3 m s −1 are detected in the column, in which case the time scale is reduced to ensure numerical stability.…”
Section: Convective Parametrisationmentioning
confidence: 99%
“…Numerical experiments confirmed that the thermal forcing of TP plays an important role on the establishment and development of the Asian summer monsoon (Broccoli and Manabe 1992;Liu et al 2001Liu et al , 2004Schneider and Bordoni 2008;Wu et al 2012b;Tang et al 2013;Chen et al 2014). In the preceding spring season, the surface thermal (ISMI).…”
mentioning
confidence: 73%